Bisexuality and the Western Christian Church The Damage of Silence - Shepherd, Carol A.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This book critically examines the lived experiences of bisexual Christians across a range of Christian traditions in the UK and the USA. Shepherd assesses whether current data on elevated rates of depressive illnesses among bisexual people also apply to the bisexual Christian community. Drawing on data collected by the author on bisexual Christians across the lifespan, the book uncovers shocking incidences of biphobia and bi erasure in the Church. Widespread ignorance among pastors of middle sexualities outside of the hetero-/homonormative binary is revealed as well as a corresponding absence of appropriate support resources. Bisexuality and the Western Christian Church will be of interest to students and scholars across a range of disciplines, including gender studies, applied theology, sociology and social psychology. It is also important reading for clergy, and LGBT faith organisations. With a Foreword by Eric Anderson, Professor of Sport, Masculinities, and Sexualities, University of Winchester, UK.
1. Introduction: A Conspiracy of Silence, Bisexuality and Christianity -- 2. Why be happy when you can be normal? Heteronormativity and Worship in the Western Christian Church -- 3. Too Hot to Handle: A Denominational Sweep of Bisexual Erasure in the Church -- 4. The Damage of Silence: Bisexual Christians discuss mental health -- 5. Intersectional Identities: Bisexual Christians discuss self-actualisation and spirituality -- 6. Great is Thy Faithfulness: Bisexual Christians discuss non-monogamy and the Bible -- 7. The Church doesn't know what to do with us: Bisexual Christians in the UK discuss church life -- 8. It's just crap: Bisexual Christians in the USA discuss church life -- 9. The Silent B: Pastors and Educators discuss bisexuality and bisexual provision -- 10. Believing Out Loud: Pastors and Educators discuss affirming practice -- 11.Prudery, Primates and Public Conveniences: Specific challenges faced by Pastors and Educators.-12. Conclusion. .
Keywords: Ethnology; Religion and sociology; Psychology and religion; Sociocultural Anthropology; Sociology of Religion; Psychology of Religion and Spirituality